Antibiotic prescription assessment in geriatrics using anatomical therapeutic chemical/defined daily dose classification and World Health Organization-essential medicines list AWaRe guidelines: a prospective and observational study - Ezika, Francis; Ramaiah, Balakeshwa; George, Blessy K.; Thomas, Shibi M.; George, Jeeva (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Geriatric patients are individuals with compromised overall functioning. The objective of this study was to assess the prescribing pattern and evaluate the therapeutic efficacy of the prescribed antibiotics. Methods: The prescribed antibiotics were grouped using anatomical therapeutic chemical classification (ATC) and World Health Organization defined daily dose (WHO DDD)/100-bed days was calculated to analyse consumed antibiotics. The neutrophils and lymphocyte count before and after therapy was used to assess the therapeutic efficacy. Results: Disease frequency was categorised using the International classification of disease (ICD-11) which reported 126 diseases, with 50 cases grouped under respiratory system. Selection of antibiotic was mainly definitive (37.14%) with dual therapy (55.71%) and with antibiotic sensitivity test (61.43%). Cephalosporins, was the most prescribed antibiotic class, specifically ceftriaxone. For every 100 bed days, 6.7 DDD of antibiotics were consumed in which 103 antibiotics were administered via intravenous route and 42 oral routes. The deviation of prescribed daily dose (PDD) from the DDD was performed for prescribed antibiotics of varying doses. Significant percentage deviation was observed for azithromycin (-70%) and piperacillin+tazobactam (-4.79%). The negative sign of the deviation indicates that the mean PDDs were higher than their respective WHO DDD. Furthermore, 81.38% of consumed antibiotic was from watch category of WHO essential medicine list (EML). Interestingly, the decrease in neutrophils and increase in lymphocytes prove the therapeutic efficacy of antibiotics. Conclusions: Watch antibiotics was the most prescribed and therapeutic efficacy was frequent with dual antibiotics therapy and in monotherapy of piperacillin-tazobactam.